2017
DOI: 10.3390/nu9111251
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Amino Acid Abnormalities in Chronic Heart Failure. Mechanisms, Potential Risks and Targets in Human Myocardium Metabolism

Abstract: The goal of this study was to measure arterial amino acid levels in patients with chronic heart failure (CHF), and relate them to left ventricular function and disease severity. Amino acids (AAs) play a crucial role for heart protein-energy metabolism. In heart failure, arterial AAs, which are the major determinant of AA uptake by the myocardium, are rarely measured. Forty-one subjects with clinically stable CHF (New York Heart Association (NYHA) class II to IV) were analyzed. After overnight fasting, blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 53 publications
8
59
1
Order By: Relevance
“…body needs and the serum BCAA concentration was significantly lower than in healthy controls. 13 In the present study, lymphocyte count, hemoglobin, albumin, total cholesterol, and CONUT score, which are widely used for evaluating nutritional status, were not associated with decreased SMI. Hemoglobin and albumin have been shown to be associated with skeletal muscle mass, 3,14 but those studies showed the association at the same observation point and did not refer to the association with future changes in skeletal muscle mass.…”
Section: Resultssupporting
confidence: 38%
“…body needs and the serum BCAA concentration was significantly lower than in healthy controls. 13 In the present study, lymphocyte count, hemoglobin, albumin, total cholesterol, and CONUT score, which are widely used for evaluating nutritional status, were not associated with decreased SMI. Hemoglobin and albumin have been shown to be associated with skeletal muscle mass, 3,14 but those studies showed the association at the same observation point and did not refer to the association with future changes in skeletal muscle mass.…”
Section: Resultssupporting
confidence: 38%
“…Data obtained from this sample of patients were compared, and statistical differences were evaluated with the findings of a study conducted on a group of 8 healthy volunteers. 19,20 Dry weight and target weight were calculated on the basis of both intradialytic and extradialytic clinical assessment and on total body water values determined by means of bioimpedance analysis.…”
Section: Populationmentioning
confidence: 99%
“…The AA concentration was expressed in both micromol/L and in mg/dl and compared in our laboratory with standard values; data obtained in these studies were subsequently compared statistically using the same laboratory procedure with those of 8 healthy volunteers in whom AA arterial concentrations had been determined. 19,21 Twenty AAs were determined, although analysis was limited to total AAs (TAAs), essential AAs (EAAs) including branched chain AAs (BCAAs), nonessential AAs (NEAAs), and the ratio of all classes of AA/TAAs.…”
Section: Amino Acid Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The human heart uses a large number of free amino acids) as regulators of both myocardial protein metabolism and energy metabolism [41]. The dependence of the myocardium on the amino acid fund of the heart increases with heart failure due to the high activity of the anabolic in the myocardium and the lack of energy for cardiomyocytes.…”
mentioning
confidence: 99%